Detection of Faults Using Digital Image Processing Technique - Patel, Jagrti; Jain, Meghna; Dutta, Papiya (Asian Journal of Engineering and Applied Technology, 2013)
This paper presents an approach to automatic detection of fabric defects using digital image processing. In Textile industry automatic fabric inspection is important to maintain the quality of fabric. Fabric defect detection is carried out manually with human visual inspection for a long time. This paper proposes an approach to recognize fabric defects in textile industry for minimizing production cost and time. Fabric analysis is performed on the basis of digital images of the fabric. The recognizer acquires digital fabric images by image acquisition device and converts that image into binary image by restoration and threshold techniques. This paper introduces a method which reduces the manual work. This image processing technique is done using MATLAB 7.10. This research thus implements a textile defect detector with system vision methodology in image processing.